Oil pulling therapy : detoxifying and healing the body through oral cleansing - Fife, Bruce, 1952- (Piccadilly Books, 2008)
Explains a revolutionary new treatment that can lead to a cure for many chronic health problems by combining the wisdom of Ayurvedic medicine with modern science to improve the health of your teeth and gums.